Rola kultury organizacyjnej w zarządzaniu bezpieczeństwem systemu informacyjnego przedsiębiorstwa - Nowicki, Adam; Rot, Artur (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The rapid progress in the area of information technology brings new threats of information disclosure. The subject of IS/IT security has become very significant. Every organization has to apply adequate methods, tools and organizational requirements to protect its information resources. The technical safeguard is not any more enough protection. It is necessary to choose different tools and methods of protection and finally to manage them in a proper way. The information system security management has to be examined not only in technological aspects, but also in social, organizational, economical and legal. It should be undertaken by interdisciplinary team of specialists. So it is necessary to take into consideration not only technological area of IS security management, but also organizational problems, especially connected with organizational culture in the enterprise. The article presents the essence and the importance of the information system security management. Its aim is also to show the meaning of the organizational culture and its role for information system security. The authors pointed out in the paper that the process of IS security management is closely connected with the organization management and that it should be the element of business and IT strategy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 421-434